The Translator as Literary Critic? Alexandre Vialatte’s Battling le Ténébreux Through the Eyes of the Translating Subject - Frances Egan (Itinéraires)
Historically, the translator has effaced herself to reproduce the author’s voice and the original text. Recent research has rendered the translator visible in translation studies but less so in literary studies. I propose engaging with the translating subject and the translator’s imaginary for the purposes of literary analysis. If literature is a product of the writer’s personal encounter with words, at the threshold between individual and social existence, the translator’s experience is uniquely inter-subjective. The wrestle for meaning between writer and translator, across times, languages, and cultures, warrants attention in literary studies. This article draws from my own experience translating Alexandre Vialatte’s novel Battling le ténébreux ou La mue périlleuse (1928) into English. Instead of analyzing or justifying my reproduction of the original text, I articulate the obstacles to translation—ambiguities, cultural and ideological differences, intertextuality—for a study of the underlying intention of the original text and a vision of its potential afterlives today.